Henry of Harclay’s Commentary on the Second Book of the Sentences. With an Edition of Harclay’s Quaestio de potentia materiae (Sent. II d. 12 q. 1) - De Pascalis, Alessandro (Bulletin de Philosophie Médiévale, 2024)
Abstract The present contribution focuses on Harclay’s Parisian Commentary on the Sentences and is divided into two sections. The fi rst section (§1) is devoted to the attribution to Harclay of a Commentary on the second book of the Sentences, a controversial issue among scholars for decades. In this fi rst section, after having reconstructed in more detail the status quaestionis about the attribution of the Commentary contained in the ms. BAV, Borgh. 346, I will present new evidence in support of its attribution to Henry of Harclay. The second section (§2) is devoted to an analysis of the manuscript tradition of Harclay’s Commentary, shedding light in particular on its indirect tradition, which is indispensable – as we shall see – for any editorial project. This section also contains an editorial Appendix with the text of Harclay’s Sent. II d. 12 q. 1, in which the Author provides his point of view on the topic of prime matter. This appendix is preceded by a brief analysis of the philosophical contents of the question.